2011
DOI: 10.1093/bioinformatics/btr371
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of phytoene synthase and its promoter reveals hints for regulation mechanisms of carotenogenesis in Duanliella bardawil

Abstract: jgjiang@scut.edu.cn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Therefore, the glycerol synthesis or degradation in D. salina treated by salt stress was due to the synergistic effect of four enzymes, which were propitious to the glycerol metabolism for osmotic adjustment of D. salina to respect to salt stress, and G3pdh play the key role in glycerol metabolism. In our previous study, it was found that several candidate motifs of the promoter of phytoene synthase (Psy), the first regulatory point in carotenogenesis in Dunaliella bardawil , exhibited salt-induced characteristics [27]. Psy is recognized as the rate-limiting enzyme in carotenoids synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the glycerol synthesis or degradation in D. salina treated by salt stress was due to the synergistic effect of four enzymes, which were propitious to the glycerol metabolism for osmotic adjustment of D. salina to respect to salt stress, and G3pdh play the key role in glycerol metabolism. In our previous study, it was found that several candidate motifs of the promoter of phytoene synthase (Psy), the first regulatory point in carotenogenesis in Dunaliella bardawil , exhibited salt-induced characteristics [27]. Psy is recognized as the rate-limiting enzyme in carotenoids synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we isolated the promoter region of Dbpsy and found a cis-acting element candidate nominated as the GT-1 motif potentially involved in the hyperosmotic expression of psy (Lao et al, 2011). We believed that some vital CRTs responsible for b-carotene biosynthesis would be up-regulated under hyperosmolarity exerted by salt stress.…”
Section: Different Induction Characteristics Of Crts Might Correlate mentioning
confidence: 99%
“…Further knowledge on its regulation mechanisms for massive accumulation of b-carotene in response to salt stress remains to be discovered. Our previous study on the D. bardawil psy (Dbpsy) promoter region implied various regulatory elements involved in the transcriptional expression of the Dbpsy gene (Lao et al, 2011). It seems that the regulation of many key carotenogenic genes (crts) is partly attributed to related transcriptional regulatory elements residing in the promoter regions; therefore, in this study, we attempted to isolate the promoter and terminator of Dbzds and subsequently used them to express a fusion protein, fusion of Zeocin resistance gene (BLE) to the enhanced green fluorescent protein (EGFP), in D. bardawil.…”
mentioning
confidence: 99%
“…In Duanliell bardawil and D. salina it was suggested that variation at the N-terminus may be accountable for fine tuning of PSY in elucidating the regulation mechanisms. However, the C-terminus of the PSY protein is special and contains the Trans-IPPS-H domain having aspartate rich region I, II (DELVD) and (DVGED) as conserved motifs as well as a substrate binding domain with a catalytic function (Lao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%